Reception Analysis of Beauty Standards of Skincare Advertisements on Instagram @skingame - Maharani, Putri Ardia Dewi; Aisyah, Vinisa Nurul (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2023)
Purpose: This research aims to find out how male and female students interpret or accept the content of messages on the @skingame Instagram video reel campaign upload. Methodology: This research uses a descriptive qualitative approach. The sampling technique used purposive sampling, and data validity was used using source triangulation. Data collection techniques used video content analysis and in-depth interviews. The theory used in the research is Stuart Hall's reception theory. This theory has three categories in audience interpretation : dominant reading, negotiated reading, and oppositional reading. Results: The video content analysis research shows that @skingame advertisements emphasize beautiful women who have self-confidence, love, and accept themselves as they are. @skingame also features models who have unusual physical characteristics to counter the meaning of beauty, which usually only focuses on material conditions. Applications/Originality/Value: As for the differences in this study, the advertisements used in previous studies included traditional short-duration advertisements. The advertisements used in this study are modern advertisements uploaded to digital platforms.